n silicoanalysis of 2A protease as a prophylactic and therapeutic target against Hand, Foot, and Mouth disease - Sia Bhatia; Kavleen Kaur
Enteroviruses, particularly EV-71, are responsiblefor the major periodic outbreaks of Hand, Foot and Mouth disease in children. To mitigate the severity of disease in pediatric populations, developing prophylactic and therapeutic agents is critically important. The present in silicostudy focuses on EV-71 2A protease as the putative target for predicting novel drugs and epitope-based vaccines against HFMD. Various natural compounds, viz. flavonoids, terpenoids, and phenolics, were screened using the H-Dock molecular docking server to analyse their binding affinities with 2A protease. Flavonoids such as protopanaxatriol (-148), Luteolin (-141), and Resibufogenin (-140) were identified as the potent inhibitors of 2A protease, based on their docking scores being comparable to that of known inhibitor CW-33(-155). Further, the bioinformatics approach was also used to construct a multi-epitope polypeptide that contains T-cell and B-cell epitopes of 2A protease alongside adjuvants and linkers to improve immunogenicity. The designed vaccine construct was further validated based on scores of immunological parameters, viz. allergenicity, antigenicity, solubility and physicochemical properties. Molecular docking studies with immune receptors reveal binding scores of -213 for TLR3, -217 for TLR5, and -233 for TLR8, indicating a promising immune stimulatory response. However, futurein vitroand animal studies will be essential to establish this research as a benchmark in terms of drug design and vaccine development